Computer analysis of dynamic reliability of some concrete beam structure exhibiting random damping - Bredow, Rafał; Kamiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
An efficiency of the generalized tenth order stochastic perturbation technique in determination of the basic probabilistic characteristics of up to the fourth order of dynamic response of Euler-Bernoulli beams with Gaussian uncertain damping is verified in this work.
Keywords: reliability analysis; Stochastic Finite Element Method; generalized stochastic perturbation technique; forced vibrations; Runge-Kutta-Fehlberg method